Treatment of Common Wart Using a Classical Siddha Formulation Sirattai Thylam: A Case Report (International Journal of Ayurveda and Pharma Research, 2022)
Siddha system of medicine is the philosophy-based medicine that deals with holistic approach to health and soul basically it is a way of life that emphasizes positive mindfulness. The essential life style for healthy living has been instructed in Siddha system, according to the geographical and seasonal varieties. As per Siddha concept there is 32 internal and 32 external medicines. Thylam (medicated oil) was popularly used for various ailments us Mudi thylam, Kudi thylam, Pidi thylam, Thulai thylam, Silai thylam. Sirattai Thylam is prepared by Kuzhi thylam method (destructive distillation method). It can be used for Naatpatta thole noigal (chronic skin diseases), Sori (itches), Padar thaamarai (ring worm), Padaigal (eczema), Thole thadippu (thickening of skin), Useful in mosquito bite scars, sun tan, white heads, sensitive skin, fungal infections. This case study addresses the successful treatment “the wart" (It's a local outgrowth of the epidermal layer of the skin) using Sirattai Thylam.